Standards to ensure the effectiveness of language teaching and the controls for teaching them in UAE - Shaheen, Ranya Ahmed Rashid (Journal of Humanities & Social Sciences, 2022)
The research paper aimed to clarify the criteria for the effectiveness of language teaching, what applied linguistics offers in language education, how the UAE began to take serious steps to include them in its curricula, and how it tries to answer the two important questions in language education. What do we know? and how?Therefore, the descriptive-analytical method was used. I referred to the experience of the Ministry of Education in introducing the second language, and the experience was applied in the Emirate of Abu Dhabi and Ras Al Khaimah to benefit from the experiences they provided from a distance while clarifying the impact of the pandemic on education.The study was divided into an introduction, two parts and a number of demands. The first topic: the reality of the relationship between linguistics and education, and the most prominent difficulties in teaching languages from a distance.The second topic: The mechanisms of developing the language teaching methodology in the United Arab Emirates were discussed.In the conclusion, the results were presented; Where I found that teaching languages falls under applied linguistics serving the educational arena, but we need to transfer theoretical knowledge to a realistic ground and that this application supports modern visions that keep pace with every change on the ground, and that we make linguistic theories a focus for change and renewal, as it needs to A political decision that serves the teaching-learning process, in parallel with the development of curricula and pedagogies with a periodic mechanism to follow up on each development and change, as well as the need to include virtual learning as a live alternative to distance or real education; To bring the virtual experience closer to the students' minds.
Keywords: applied linguistics; educational languages; educational; distance learning